Development of Three Different NK Cell Subpopulations during Immune Reconstitution after Pediatric Allogeneic Hematopoietic Stem Cell Transplantation: Prognostic Markers in GvHD and Viral Infections - Huenecke, Sabine; Cappel, Claudia; Esser, Ruth; Pfirrmann, Verena; Salzmann-Manrique, Emilia; Betz, Sibille; Keitl, Eileen; Banisharif-Dehkordi, Julia; Bakhtiar, Shahrzad; Königs, Christoph; Jarisch, Andrea; Soerensen, Jan; et al. (Frontiers in Immunology, 2017)
Natural Killer (NK) cells play an important role following allogeneic hematopoietic stem cell transplantation (HSCT) exerting graft-versus-leukemia/ tumor (GvL/T) effect and mediating pathogen specific immunity. Although, NK cells are the first donor derived lymphocytes reconstituting post HSCT, their distribution of CD56++CD16- (CD56bright), CD56++CD16+ (CD56intermediate=int) and CD56+CD16++ (CD56dim) NK cells is explicitly divergent from healthy adults, but to some extend comparable to the NK cell development in early childhood. The proportion of CD56bright / CD56int / CD56dim changed from 15% / 8% / 78% in early childhood to 6% / 4% / 90% in adults, respectively. Within this study we first compared the NK cell reconstitution post-HSCT to reference values of NK cell subpopulations of healthy children. Afterwards, we investigated the reconstitution of NK cell subpopulations post-HSCT in correlation to acute and chronic GvHD as well as to viral infections. Interestingly, after a HSCT follow-up phase of 12 months, the distribution of NK cell subpopulations largely matched the 50th percentile of the reference range for healthy individuals. Patients suffering from acute and chronic GvHD showed a delayed reconstitution of NK cells. Remarkably, within the first two months post-HSCT, patients suffering from acute GvHD (aGvHD) had significantly lower levels of CD56bright NK cells compared to patients without viral infection or without GvHD. Therefore, the amount of CD56bright NK cells might serve as an early prognostic factor for GvHD development. Furthermore, a prolonged and elevated peak in CD56int NK cells seemed to be characteristic for the chronification of GvHD. In context of viral infection, a slightly lower CD56 and CD16 receptor expression followed by a considerable reduction in the absolute CD56dim NK cell numbers combined with reoccurrence of CD56int NK cells was observed. Our results suggest that a precise analysis of the reconstitution of NK cell subpopulations post-HSCT might indicate the occurrence of undesired events post HSCT such as severe aGvHD.